2020
DOI: 10.3390/ijms21082970
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium, Not Carbon Monoxide, Inhibits the Procoagulant Activity of Atheris, Echis, and Pseudonaja Venoms

Abstract: The demonstration that carbon monoxide releasing molecules (CORMs) affect experimental systems by the release of carbon monoxide, and not via the interaction of the inactivated CORM, has been an accepted paradigm for decades. However, it has recently been documented that a radical intermediate formed during carbon monoxide release from ruthenium (Ru)-based CORM (CORM-2) interacts with histidine and can inactivate bee phospholipase A2 activity. Using a thrombelastographic based paradigm to assess procoagulant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 34 publications
(187 reference statements)
0
29
0
Order By: Relevance
“…69 Thus, a radical intermediate formed during carbon monoxide release from ruthenium (Ru)based CORM-2 is likely responsible for the CORM-2-mediated inhibition of diverse snake and lizard venoms. 70,71 Other findings also demonstrated that CORM-2 activates nonselective cation current in endothelial cells independently of carbon monoxide release, 72 and the potent antimicrobial and cytotoxic properties of CORM-3 are produced by Ru-based CORM-3. 73 Regarding the analgesic effects produced by CORM-2 and CORM-3 in animals with chronic pain, the treatments with inactive CO-RMs (iCORM-2 and iCORM-3) did not produce any antiallodynic and antihyperalgesic effects during neuropathic pain.…”
Section: T a B L E 1 The Antinociceptive Effects Of Carbon Monoxide Amentioning
confidence: 94%
“…69 Thus, a radical intermediate formed during carbon monoxide release from ruthenium (Ru)based CORM-2 is likely responsible for the CORM-2-mediated inhibition of diverse snake and lizard venoms. 70,71 Other findings also demonstrated that CORM-2 activates nonselective cation current in endothelial cells independently of carbon monoxide release, 72 and the potent antimicrobial and cytotoxic properties of CORM-3 are produced by Ru-based CORM-3. 73 Regarding the analgesic effects produced by CORM-2 and CORM-3 in animals with chronic pain, the treatments with inactive CO-RMs (iCORM-2 and iCORM-3) did not produce any antiallodynic and antihyperalgesic effects during neuropathic pain.…”
Section: T a B L E 1 The Antinociceptive Effects Of Carbon Monoxide Amentioning
confidence: 94%
“…In response to these new findings [ 7 , 8 ], it was subsequently reported that purified phospholipase A 2 isolated from bee venom was inhibited by CORM-2 via a CO-independent mechanism, with inhibition of the venom by CORM-3 (tricarbonylchloro(glycinato)ruthenium) likely also dependent on a Ru(II)-based mechanism [ 9 ]. Thereafter, anticoagulant metalloproteinase activity in venoms collected from mambas was found to be inhibited by CORM-2 by a similar CO-independent mechanism [ 10 ], and, finally, the procoagulant activity exerted by metalloproteinases and serine proteases was found to be inhibited by CORM-2 and ruthenium(III) chloride (RuCl 3 ) [ 11 ]. Thus, as suggested by the works of the past several months [ 9 , 10 , 11 ], it is the ruthenium species, not CO, that are binding to key anticoagulant/procoagulant venom enzymes in a heme-independent and perhaps irreversible fashion.…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, anticoagulant metalloproteinase activity in venoms collected from mambas was found to be inhibited by CORM-2 by a similar CO-independent mechanism [ 10 ], and, finally, the procoagulant activity exerted by metalloproteinases and serine proteases was found to be inhibited by CORM-2 and ruthenium(III) chloride (RuCl 3 ) [ 11 ]. Thus, as suggested by the works of the past several months [ 9 , 10 , 11 ], it is the ruthenium species, not CO, that are binding to key anticoagulant/procoagulant venom enzymes in a heme-independent and perhaps irreversible fashion.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations